Transitioning to concept-based curriculum and instruction : how to bring content and process together - Erickson, H. Lynn; Lanning, Lois A. (California : Corwin, Thousand Oaks, 2014)
What keeps us going as teachers? What makes teaching the best job in the world? When asked this question, many teachers will talk about that light coming on in students' eyes, or the 'ah-ha' moment when students 'get it'. Lynn Erickson and Lois Lanning have provided me with some of my personal 'ah-ha' moments over the last few years. They have helped me to see how we can help students to 'get it', to be engaged in their learning and to understand how to transfer and apply their knowl-edge, understanding and skills in meeting complex global challenges. As a schoolboy in the 1980s I learned about isotopes as my teachers had learned it by rote. Despite doing well in all of my science/chemistry exams I never really understood what an isotope is, or why I needed to know. By the age of 23 I had become a science teacher and began to teach about isotopes. After the first attempt to transfer my old school notes from my pen to the students' brains, I realized that they simply didn't get it. I looked at the patterns around the periodic table, at the way in which scientists use models to better describe phenomena and noted that isotopes were pretty useful in everyday life, for food preservation, health treatments and so on. My teaching of isotopes was transformed, but so too was my own understanding_ so much that I now understand isotopes and I no longer rely on those notes my teacher made me repeat in the 1980s! This is the transformative effect of concept-based teaching and learning- the level of understanding, application and engagement lead to a far more satisfying experience for students and teachers.
1. Curriculum design : from an objectives-based to a concept-based model -- 2. Two-dimensional versus three-dimensional curriculum models -- 3. The structure of knowledge -- 4. The structure of process -- 5. The developing concept-based student -- 6. The developing concept-based student -- 7. What do teachers need to understand about concept-based pedagogy? -- 8. What do principals and instructional coaches need to understand about Implementing and sustaining concept-based curricular and instructional models in their schools? -- 9 What do district leaders need to understand about concept-based Curriculum designs? -- 10. Summary and the road ahead.
Includes bibliographical references and index.
Keywords: CURRICULUM PLANNING; EDUCATION PLANNING